Does the Implementation of the Schengen Agreement Boost Cross-Border Commuting? Evidence from Switzerland - Angela Parenti; Cristina Tealdi (Institute of Labor Economics (IZA), 2019)
In this paper we study the effects of Switzerland implementing the Schengen agreement on cross-border commuting from regions of neighbouring countries. As vehicles are allowed to cross borders without stopping and residents in border areas are granted freedom to cross borders away from fixed checkpoints, commuting costs are severely reduced. Using data from the European Labour Force Survey, we estimate that the individual probability to cross-border commute to Switzerland in response to this policy has increased among inter-regional commuters in the range between 3 and 6 percentage points, according to different model specifications. Our result is particularly important due the meaningful policy implications, in a time in which the Schengen agreement is under scrutiny and at risk of termination.
Keywords: D04; J61; R10; R23; 330; Schengen agreement; labour mobility; commuting costs; policy change